Dominant bacterial diseases in the extensive and semi-intensive animal breeding and their treatment method by ethnoveterinary medicine in Benin - Clément Abiola Ogni, Marc Kpodekon, Jacques Dougnon, Hospice Dassou, Judicaël Enagnon Goussanou, Cyrille Boko, Bénoît Koutinhouin, Issaka Youssao, Akpovi Akoegninou (Journal of Applied Pharmaceutical Science, 2016)
In Africa, various herbal medicines are used in treatment of animal diseases. This study aims to identify the medicinal plants that are often used to cure bacterial diseases in domestic animals, in order to promote their rational and sustainable use. The work was performed by working with 787 breeders in the 8 agro-ecological zones of Benin, from June to December 2013. An ethnobotanical survey has identified 32 medicinal plants species among which Afzelia africana, Crossopteryx febrifuga, Albizia chevalieri, Khaya senegalensis, Mangifera indica and Entada africana are used for bovine pasteurellosis. The bronchitis is treated by 11 species of medicinal plants which include Allium sativum, Garcinia kola, Terminalia laxiflora, Zanthoxylum zanthoxyloides and Detarium microcarpum. For infectious coryza treatment, 8 plants have been identified among which, we have Securinega virosa, Capsicum annuum, Anacardium occidentale and Vitellaria paradoxa. About cutaneous streptothricosis, 3 plants (Zea mays, Piliostigma thonningii and Parkia biglobosa) were cited for its treatment. Contagious bovine peripneumonia is treated by 3 plants (Tamarindus indica, Oxythenanthera abyssinica and Khaya senegalensis). Avian salmonellosis is also treated by 3 plants (Bridelia ferruginea, Cissus quadrangularis and Ocimum gratissimum). Concerning Blackleg and enterotoxemia, they are respectively treated by Aganope stulhmannii and Ocimum gratissimum.
Keywords: Bacterial diseases, breeding in Benin, ethnoveterinary medicine, medicinal plants.